Expanded full thickness skin graft to repair scar and scar contractures: a descriptive case series - Ghag, Nitin V.; Aggarwal, Aditya; Singh, Hardeep; Singh, Sukhdeep; Mahendru, Sanjay; Brajesh, Vimalendu; Khazanchi, Rakesh; Kothari, Umang (International Surgery Journal, 2020)
Management of deep burns/trauma scars has always been a challenge. Seven patients with burn/trauma scar were treated with expanded full thickness grafts (EFTSGs). In stage one, tissue expanders were implanted at the donor sites and expansion with saline was done as an out-patient for 4-5 months. In stage two, the scar was excised and secondary wound was repaired with EFTSGs. Total of 8 EFTSGs were harvested from various donor sites. After stage one there was good blood supply noted in all the expanded skin flaps. After stage two, EFTSGs survived in all; except for partial skin necrosis in the leg of one patient. The graft take were excellent in color-match, texture and elasticity. There was a significant improvement in function and aesthetic aspect in all the cases. EFTSGs is an effective solution to repair effectively scar and scar contractures due to excellent cosmetic and functional recovery.